Effect of moist heat sterilization on phytochemical content, anti-oxidant property and microbial sterility of black rice bran - Noppawat Pengkumsri (2018)
© 2015, Journal of Pure and Applied Microbiology. All rights reserved. Rice bran (RB) contains a variety of bioactive components with pharmaceutical values. Black RB (BRB) is rich in phytochemical content. The sterilization process affects the quality of the RB bioactive constituents. The aim of this study was to evaluate content and activity of phytochemicals of BRB after moist heat sterilization. BRB samples were subjected to moist heat at different temperature and time followed by polar and non-polar extractions. The yield of BRB oil was not significantly affected by sterilization. The sterility of treated BRB was evaluated by plate count method. BRB treated at 90 °C for 15 min showed no detectable level of bacterial load. The total phenolic, flavonoid, anthocyanin, and γ-oryzanol content of the BRB extracts were assessed by colorimetric, and HPLC methods. The total phenolic, flavonoid, anthocyanin, and γ-oryzanol content of the treated BRB were decreased with respect to the increased temperature and time. The antioxidant property of sterilized BRB was reduced compared to the control. The present study also suggested that the moist heat at 90 °C for 15 min is the optimal condition for RB sterilization with negligible loss in quality, which can be further subjected to the detailed pharmacological analysis without any microbial contamination.